The Influence of Employee Motivation on the Quality of Administrative Services at the Leihitu Sub-District Office, Central Maluku Regency - Malawat, Lestari; Stanislaus Kostka Ohoiwutun; Ivonny Yeany Rahanra (Journal of International Multidisciplinary Research, 2025)
Public service quality is one of the fundamental indicators in assessing the performance of government institutions, especially at the district level where direct interactions with citizens take place. This study aims to analyze the influence of employee motivation on the quality of administrative services at the Leihitu Sub-district Office, Central Maluku Regency. The research employs a quantitative approach with an explanatory design to identify causal relationships between variables. The population in this study consists of all employees involved in administrative services, and total sampling was used due to the manageable number of staff. Data were collected through a structured questionnaire using a Likert scale to measure motivation and service quality indicators. The data were analyzed using descriptive statistics and linear regression to determine the effect of motivation on service quality. The results show that employee motivation significantly and positively influences administrative service quality. Employees with higher intrinsic and extrinsic motivation tend to demonstrate better responsiveness, discipline, communication, and consistency in carrying out public service functions. The study concludes that strengthening motivation is essential to improve public service performance. Therefore, organizational leaders are encouraged to enhance work motivation through recognition, supportive leadership, fair reward systems, and professional development opportunities to ensure services meet community expectations.